Relaksasi Nafas Dalam Untuk Mengurangi Nyeri Pada Pasien Dengan Gastritis - Putri, Intan Prila Pratama Budiono, Abi Muhlisin, SKM, M.Kep, Supratman, Ph.D (2017)
Gastritis is an inflammation of the gastric mucosa is characterized by discomfort in the upper abdomen nausea vomiting due to problem in asthma increase stomach right because of the delay meals or like to eat spicy food so there needs to be awareness in people that only as well as the role of families in caring for member families suffering from gastritis and also the role of nurse to reduce the occurrence of complication in patient with gastritis.this research uses methods of nursing care from assesment and evaluation. Instrument used were interview to all member of the family and especially to client who have gastritis to obtain data that truth thought case studies.the purpose of this study was to relieve their pain Tn family j with gastritis client. the result showed no significant asociation between pain and anxiety reduction effort (by relaxing your breath and guide imagery )to prevent pain does not occur in patient.